Retaining customers through Islamic relationship marketing practice: findings from Malaysian takaful industry - Che Mohd Salleh, Marhanum (2014)
In recent times, the ability to maintain good and quality relationships with customers has become a competitive advantage for a company. In this context, a few marketing scholars have suggested that retaining customers is much more profitable than acquiring new ones. Parallel with the objective of Relationship Marketing (RM) which is to minimize the lost of profitable customers by ensuring future customer retention, this research is conducted to introduce a new concept of Islamic Relationship Marketing (IRM) and investigate its influence towards future customer retention. By selecting 755 customers of Malaysian Takaful industry and utilising stuctural equation modelling as statistical method to achieve the research objective, it is found that customers in this industry intend to remain with the same Takaful operator and agent for long term period given that they practice the Islamic ethical behaviour and build strong relational bonds (social, structural, and financial bonds) with the customers. Besides that, the application of social exchange theory in the research framework have been proven in this research whereby the practice of Islamic relationship marketing in the Takaful industry would give positive affect towards future customer retention. Overall, the results of this research would urge Takaful operators and agents to be more concerned with the marketing approach that they utilise which basically must parallel with the maqasid Shari’ah as to ensure future customer retention. These factors are also important in helping Takaful to remain competitive in the market for the long term.